Abundance of non-conservative microplastics in the upper ocean from 1957 to 2066 - Atsuhiko Isobe (Nature Portfolio, 2019)
The spatio-temporal distributions of these plastics are not fully characterized. Here the authors examined the sources, sinks and pathways and projected microplastic concentrations for 2066 and found that most plastics accumulate in the North Pacific, with the highest concentrations predicted in the East Asia Seas and central North Pacific.